IMPROVED LEARNING OUTCOMES OF FIQH SUBJECTS THROUGH QUIPPER SCHOOL-BASED LEARNING FOR STUDENTS OF GRADE XI IPA 2 IN MAN 1 MALANG - Nadiva, Dewinta Nisa (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
Learning activities are one of the processes where it can be said to be successful if the students have high intelligence and grades. In learning, besides being influenced by the teacher, it can also be influenced by the media, methods, and strategies used. The purpose of the study was to improve student learning outcomes in class XI IPA 2 MAN 1 Malang in fiqh subjects. This type of research is Classroom Action Research (CAR) using a quantitative approach. The data in this study were obtained from the results of observations and the results of the tasks of each cycle. Based on the results of the study showed that student learning outcomes with the help of the use of Quipper School media experienced an increase in the average student score. In the early stages the average value of students was 20.58 while the first cycle increased to 47.05 then in the second cycle there was an increase again, namely to 60.